Energy Efficiency Finance : Assessing the Impact of IFC's China Utility-based Energy Efficiency Finance Program - Independent Evaluation Group (Washington, DC: World Bank, 2012)
This evaluation assesses the performance of International Finance Corporations (IFC's) energy efficiency finance program in China aimed at stimulating energy efficiency investments through bank guarantees and technical assistance. The program's significance is underpinned by the fact that China's size, rapid economic growth, and inefficiencies in energy use make it one of the world's largest emitters of carbon dioxide (CO2.). The utilization of IFC's program has been rapid compared with other similar programs. The difference made by the program is traced along the chain of interventions: (i) at the level of banks, the program is narrowly based on one of the two partner banks, which, with the help of the program, expanded its energy efficiency lending as a new business line; (ii) at the level of energy management companies, the program's technical assistance improved the program participants' access to finance; and (iii) at the end-user level, it promoted the use of energy efficiency investments that achieved reduction of greenhouse gas emissions. The evaluation recommends areas of improvement to realize greater impact. First, the program needs to emphasize areas where the potential additionality is high, such as small enterprises. Second, the program needs to concentrate more on activities that have the potential to reduce emissions significantly, such as energy efficiency for buildings. Third, the program's subsidy elements need to be reoriented to the areas of market failure, with IFC increasing its coverage of first loss from its own resources.